PRIMARY HYDROCOELES IN INFANTS AND CHILDREN - Qureshi, Zaheeruddin; Ahmed, Sarfaraz; Haider, Irfan Zaffar; Khan, Khalid (Journal of Ayub Medical College Abbottabad, 2011)
Background: Hydrocoele is an abnormal quantity of serous fluid within the tunica vaginalis. It can be primary or secondary. The primary can in turn be congenital or acquired. Objective of this study was to see the frequency of primary hydrocoeles in children presenting to Ayub Teaching Hospital, Abbottabad. Methods: This prospective study was conducted in Surgical '˜B' Unit, Ayub Teaching Hospital, Abbottabad, from Feb 2007 to Feb 2009. All Children above 6 months age with hydrocoeles and operated were included in this study. All details were recorded on a proforma. The collected data were analysed, results calculated, and conclusions drawn. Results: In all 186 operated cases, the maximum (58, 37%) incidence was in 2-3 years age group. Injury to the vas occurred in 1 (0.7%) case, infection rate was 0% and scrotal haematoma occurred in 18% cases. Conclusion: Children with hydrocoeles should be operated after 6 months age. Herniotomy is the only satisfactory treatment and in expert hands complications are very rare. Keyword: Hydrocoeles, Herniotomy, infants